Pengembangan Penuntun Praktikum Biosistematika Tumbuhan Terintegrasi Keislaman Terhadap Nilai Religius Mahasiswa: (Development of Islamic Integrated Plant Biosystematics Practicum Guide to Students’ Religious Values) - Moh. Imam; Nanik Lestariningsih; Nurul Septiana (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study departs from the analysis of the needs of students and lecturers who stated that there is not yet available Islamically integrated plant biosystematics practicum guide because the RPS for Islamic integration-based courses and interview results show that in practical learning activities students' religious values ​​have not been maximized, this is because there are still many students in practicum activities are more likely to play around and be lazy, even most students do not study and choose the path of cheating during prites. The purpose of the study was to determine the validity, practicality and religious values ​​of students after the use of an Islamic integrated plant biosystematics practicum guide. The type of research is R&D (research and development) using the ADDIE development model. The instruments used were validation questionnaires, response questionnaires and applied observation sheets, data analysis was carried out by validity analysis, practicality analysis and student religious value analysis. The results showed that product validation for material experts got an average result of 4.35 with very valid criteria, design experts got an average result of 4.30 with very valid criteria and interpreters got an average result of 4.20 with valid criteria. . The practicality value obtained an average result of 4.40 with very practical criteria for student responses and 4.55 with very practical criteria for lecturer and practicum assistant responses. Students' religious scores got an average result of 3.99 with good criteria and the applicability reached 87.68% with very good criteria. Based on these results, the Islamic integrated plant biosystematics practicum guide can be declared valid, practical and can maximize students' religious values. Key words: Practical gyide, Plant biosystematics, Islamic Integration Abstrak Penelitian ini bertolak dari analisis kebutuhan mahasiswa dan dosen yang dilakukan yang menyatakan belum tersedianya penuntun praktikum biosistematika tumbuhan yang terintegrasi keislaman karena pada RPS mata kuliah berbasis integrasi keislmanan dan hasil wawancara yang menunjukkan dalam kegiatan pembelajaran praktikum nilai religius mahasiswa belum maksimal, hal ini dikarenakan masih banyak mahasiswa dalam kegiatan praktikum lebih cendrung bermain-main dan bermalas-malasan bahkan kebanyakan mahasiswa tidak belajar dan memilih jalan menyontek pada saat prites. Tujuan penelitian untuk mengetahui validitas, kepraktisan dan nilai religius mahasiswa setelah penggunaan penuntun praktikum biosistematika tumbuhan terintegrasi keislaman. Jenis penelitian adalah R&D (penelitian dan pengembangan) dengan menggunakan model pengembangan ADDIE. Instrumen yang digunakan adalah angket validasi, angket respon dan lembar observasi keterterapan, analisis data dilakukan dengan analisis validitas, analisis kepraktisan dan analisis nilai relgius mahasiswa. Hasil penelitian menunjukkan validasi produk pada ahli materi mendapatkan hasil rata-rata 4,35 dengan kriteria saangat valid, pada ahli desain mendapatkan hasil rata-rata 4,30 dengan kriteria sangat valid dan ahli tafsir mendapatkan hasil rata-rata 4,20 dengan kriteria valid. Nilai kepraktisan mendapatkan hasil rata-rata 4,40 dengan kriteria sangat praktis untuk respon mahasiswa dan 4,55 dengan kriteria sangat praktis untuk respon dosen dan asisten praktikum. Nilai religius mahasiswa mendapatkan hasil rata-rata 3,99 dengan kriteria baik dan keterterapannya mencapai 87,68% dengan kriteria sangat baik. Berlandaskan hasil tersebut maka penuntun praktikum biosistematika tumbuhan terintegrasi keislaman dapat dinyatakan valid, praktis dan dapat memaksimalkan nilai religius mahasiswa. Kata kunci: Penuntun praktikum, Biosistematika tumbuhan, Integrasi keislaman